The role of e-leadership in digital transformation in the organizational section of the Sumedang district Setda - Laila Dwi Mustika; Iksan Syarief Firmansyah; Rizky Ilhami (Jurnal Scientia, 2024)
Technological developments in the digital era have brought about changes in various aspects and can support a leader in carrying out e-leadership for digital transformation in administering good government and realizing excellent public services. The purpose of this research is to find out how the role of E-leadership is implemented in digital transformation in the Sumedang Regency Regional Secretariat organization. The research method uses qualitative with the data collected obtained from literature review methods, observation and interviews. Using E-leadership theory according to Van Wart at al (2019), using 6 dimensions, namely communication skills, social skills, team building skills, change management skills, technology skills and feasibility. The results of the research show that the truth dimension has worked better than other dimensions. Therefore, the role of E-leadership in digital transformation in the organizational section of the Sumedang Regency Regional Secretariat is not yet optimal in implementing the E-leadership attitude for digital transformation. There are still leaders who have not been able to utilize technology properly in administering government and carrying out the main tasks and functions that have been determined.